2015
DOI: 10.12968/bjcn.2015.20.sup4.s22
|View full text |Cite
|
Sign up to set email alerts
|

Early lipoedema diagnosis and the RCGP e-learning course

Abstract: Frequently misdiagnosed as obesity, lipoedema is chronic condition involving an abnormal build-up of fat cells in the legs, thighs and buttocks that cannot be shifted by exercise or dieting. Estimated to affect up to 11% of the female population, the condition is widely unknown by health professionals. This means women typically wait for many years before diagnosis. This allows the condition to progress unchecked, resulting in unnecessary deterioration and the development of associated comorbidities, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Individuals with anorexia overly restrict food intake to correct a distorted body image [ 19 ]. The disproportionate increase in fat accumulation on the legs in lipedema is relatively resistant to diet and exercise, which, paired with lack of awareness of this medical disorder, leads to increasing frustration [ 6 , 20 , 21 ]. The lipedema tissue on the young woman’s legs in this case did not respond to weight loss, which resulted in more unhealthy eating thoughts and behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with anorexia overly restrict food intake to correct a distorted body image [ 19 ]. The disproportionate increase in fat accumulation on the legs in lipedema is relatively resistant to diet and exercise, which, paired with lack of awareness of this medical disorder, leads to increasing frustration [ 6 , 20 , 21 ]. The lipedema tissue on the young woman’s legs in this case did not respond to weight loss, which resulted in more unhealthy eating thoughts and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of lipedema is very low among medical professionals and the general population [ 20 ]. A United Kingdom study showed 93% of patients who presented with lipedema signs and symptoms were not recognized by their physicians [ 20 ]. It is possible that awareness of lipedema could have helped the patient with body acceptance and prevented the development of anorexia.…”
Section: Discussionmentioning
confidence: 99%
“…While patients are often initially relieved to receive an accurate diagnosis for their condition, the lack of an easy solution can lead to disappointment and psychological support may be recommended. 21 24 …”
Section: Treatmentmentioning
confidence: 99%
“…Anecdotally, patients have reported finding other diets, such as the Rare Adipose Disorders (RAD) diet or antiinflammatory diets helpful; however, there is no evidence to demonstrate the effectiveness of a particular diet on lipoedema. and allied health professionals, such as physiotherapists and occupational therapists, are appropriately trained to assess, diagnose, and advise patients on the best possible treatment to manage and prevent further progression (Fetzer and Fetzer, 2015;Hardy, 2015). Provision of clinics across the UK is variable, although Lipoedema UK is compiling a register of UK NHS and private clinics that treat lipoedema.…”
Section: Healthy Eatingmentioning
confidence: 99%
“…Citing peer-reviewed articles such as Fetzer and Fetzer (2015) or Todd (2010) can be helpful in providing credible material to share with health professionals. Lipoedema UK also produces a GP information pack as well as a handbook for health professions and patients.…”
Section: Issues With Applicationmentioning
confidence: 99%